Behavior of Alkaline‐Metal Catalysts in Supercritical Water Gasification of Lignite. Issue 8 (11th July 2018) - Qu, Xuan; Zhou, Xianxian; Yan, Xiaoqiang; Zhang, Rong; Bi, Jicheng
Abstract: The efficient utilization of abundant low‐rank coals, which show high moisture and ash content, is significant for coal‐based energy systems. The gasification of Zhaotong lignite was performed with different alkaline‐metal catalysts, such as KOH, NaOH, K2 CO3, and Na2 CO3, in supercritical water. The behavior of the alkaline metal was also investigated. Potassium shows better catalytic activity than sodium. KOH not only promotes breakage of chemical bonds in the coal matrix to generate low‐molecular‐weight gases, but also alters the pore structure of the char to improve the gasification of carbon in the residue. However, potassium is partly inactivated upon reaction with minerals in coal in supercritical water gasification. In situ protection of potassium is realized by adding Ca(OH)2 under supercritical conditions. Abstract : Alkaline metals have a catalytic effect on supercritical water gasification (SCWG). Potassium shows better catalytic activity than sodium; however, potassium is inactivated upon reaction with minerals in coal in SCWG. In situ protection of potassium is realized by adding Ca(OH)2 under supercritical conditions.